The Influence of Celebrity Endorsement and Social Media Marketing on Purchase Decisions through Brand Trust - David Nur Hadi; Agus Dwi Cahya; Azwar Azwar (Research Horizon, 2026)
The rapid growth of Indonesia’s skincare industry has increased competition among local brands, prompting companies to utilize celebrity endorsements and social media marketing. This study examines the effects of celebrity endorsement and social media marketing on consumers’ purchase decisions on TikTok Shop, with brand trust as a mediating variable. The study is based on the Stimulus-Organism-Response (S-O-R) theory, which explains how external stimuli influence internal psychological states and behavioral responses. A quantitative approach was employed by collecting primary data through Likert-scale questionnaires from moisturizer consumers on TikTok Shop using purposive sampling, with data analyzed using PLS-SEM. The findings reveal that celebrity endorsement and social media marketing do not directly influence purchase decisions. However, both variables have a positive and significant effect on brand trust, which in turn positively and significantly affects purchase decisions. Furthermore, brand trust fully mediates the relationships between celebrity endorsement and purchase decisions, as well as between social media marketing and purchase decisions. These findings highlight the critical role of brand trust in translating digital marketing efforts into consumer purchasing behavior and provide practical insights for skincare brands seeking to strengthen consumer trust and drive purchase decisions.